High genetic diversity among Pseudomonas aeruginosa and Acinetobacter spp. isolated in a public hospital in Brazil - Vera Lúcia Dias Siqueira; Rosilene Fressatti Cardoso; Rubia Andreia Falleiros de Pádua; Katiany Rizzieri Caleffi-Ferracioli; Cesar Helbel; Adolfo Carlos Barreto Santos; Elisabeth Eyko Aoki; Celso Vataru Nakamura (Universidade de São Paulo, 2013)
In Brazil and other regions of the world, Pseudomonas aeruginosa and Acinetobacter spp. have emerged as important agents of nosocomial infection and are commonly involved in outbreaks. The main objective of the present study was to evaluate the genetic relationship among P. aeruginosa and Acinetobacter spp. isolated from patients in a public university hospital in northwestern Paraná, Brazil, and report their antimicrobial resistance profile. A total of 75 P. aeruginosa and 94 Acinetobacter spp. isolates were phenotypically identified and tested for antibiotic susceptibility using automated methodology. Polymyxin B was tested by disk diffusion for P. aeruginosa. Metallo-β-lactamase (MBL) was detected using a disk approximation test. Genotyping was performed using enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR). Approximately 55% of the P. aeruginosa isolates and 92% of the Acinetobacter spp. isolates were multiresistant, but none were MBL-producers. ERIC-PCR revealed the presence of small clusters of carbapenem-resistant Acinetobacter spp., most likely OXA-type carbapenemase producers. Furthermore, high genetic diversity in P. aeruginosa and Acinetobacter spp. clinical isolates was observed, suggesting that cross-transmission is not very frequent in the studied hospital. No Brasil, bem como em outras regiões do mundo, Pseudomonas aeruginosa e Acinetobacter spp. surgiram como importantes agentes de infecção nosocomial e são comumente envolvidos em surtos. O objetivo principal deste estudo foi descrever a relação genética de P. aeruginosa e Acinetobacter spp. isoladas de pacientes internados em hospital universitário público do noroeste do Paraná - Brasil e reportar o perfil de resistência dessas bactérias. Um total de 75 P. aeruginosa e 94 Acinetobacter spp. isolados foi fenotipicamente identificado e testado para a suscetibilidade aos antibióticos por metodologia automatizada. A polimixina B foi testada por difusão em disco para P. aeruginosa. Metalo-β-lactamase (MBL) foi detectada por disco-aproximação. Análise genotípica foi realizada por enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR). Aproximadamente 55% dos isolados de P. aeruginosa e 92% de Acinetobacter spp. isolados foram multirresistentes, mas nenhum foi produtor de MBL. Os resultados de ERIC-PCR revelaram pequenos grupamentos de Acinetobacter spp. resistentes aos carbapenêmicos, provavelmente pela produção de carbapenemases do tipo OXA. Além disso, alta diversidade genética entre os isolados de P. aeruginosa e Acinetobacter spp. foi observada, sugerindo que a transmissão cruzada destas espécies bacterianas não é muito frequente em nosso hospital.